Computer programs for analysis of nucleic acid hybridization, thermal denaturation, and gel electrophoresis data. - Murphy, R F (1979)
Computer programs for the analysis of data from techniques frequently used in nucleic acids research are described. In addition to calculating non-linear, least-squares solutions to equations describing these systems, the programs allow for data editing, normalization, plotting and storage, and are flexible and simple to use. Typical applications of the programs are described.